15c-4=12c+5

Simple and best practice solution for 15c-4=12c+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15c-4=12c+5 equation:


Simplifying
15c + -4 = 12c + 5

Reorder the terms:
-4 + 15c = 12c + 5

Reorder the terms:
-4 + 15c = 5 + 12c

Solving
-4 + 15c = 5 + 12c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-12c' to each side of the equation.
-4 + 15c + -12c = 5 + 12c + -12c

Combine like terms: 15c + -12c = 3c
-4 + 3c = 5 + 12c + -12c

Combine like terms: 12c + -12c = 0
-4 + 3c = 5 + 0
-4 + 3c = 5

Add '4' to each side of the equation.
-4 + 4 + 3c = 5 + 4

Combine like terms: -4 + 4 = 0
0 + 3c = 5 + 4
3c = 5 + 4

Combine like terms: 5 + 4 = 9
3c = 9

Divide each side by '3'.
c = 3

Simplifying
c = 3

See similar equations:

| -6x-3=3 | | y=44+6(1-5) | | -4x-5=5x-14 | | 2[1.5m+3]=3.5m-1 | | 3x^2+5=x^2-2 | | y-10=2x+3x | | y=-16+6(1+5) | | 5x+4-10=2x-2 | | 2x+37=12x-73 | | x+9=7x-63 | | y-10=2 | | 6x^2-7x-5=0 | | 3x^2+x=2x-6 | | 3+(-5x)=-17 | | y=94+5(1-9) | | 4(a+3.2)=9a-5.2 | | y=9+5(1+8) | | 4x-5+5x-15=180 | | 6(-4-7a)+4=28+6a | | 2x^2-3x=20 | | 6b-2b+6=-10 | | 205=5(1+5v) | | 8-4d=12 | | y=8+6(1-5) | | -35+7x=8(x-4) | | 2[a-1]=3[a+1] | | 9a-(15a-(3b+7a)+(-8b+a)+12b)= | | y=5+5(1-8) | | 7(x+5)-4=87 | | .6(2m-10)=.6m+10 | | 12-4y=16x | | y=-25+4(1+5) |

Equations solver categories